THE EFFECTS OF VOCABULARY MASTERY AND READING INTEREST TOWARDS THE STUDENTS’ NARRATIVE WRITING SKILL - Linda Manullang; Supeno Supeno (Universitas Indraprasta PGRI, 2020)
This research is aimed at finding the effect of vocabulary mastery and reading interest toward the students’ narrative writing skill. The hypothesis of this study includes: 1). There is a collaborative significant effect of the vocabulary mastery and reading interest toward the students’ narrative writing skill; 2). There is a significant effect of the vocabulary mastery toward the students’ narrative writing skill; and 3). There is a significant effect of the reading interest toward the students’ narrative writing skill. The method of the research is a double regression linear by descriptive survey analysis applying some samples from a number of population and using questionnaire and tests instrument for data collection. The number of the samples is 80 students of grade ten (X) who are students of the State Vocational High School in West Jakarta.